2020
DOI: 10.2478/acve-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Analysis of the Spread of ASF in the Russian Federation in 2017-2019

Abstract: AbstractCurrently, African swine fever (ASF) is one of the biggest global economic challenges in Europe and Asia. Despite all the efforts done to understand the mechanism of spread, presence and maintenance of ASF in domestic pigs and wild boar, there are still many gaps in the knowledge on its epidemiology.This study aims to describe spatial and temporal patterns of ASF spread in wild boar and domestic pigs in the country during the last three years. Methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…Spatial analysis of data from the RF obtained between 2007 and 2013 revealed clusters of ASF in wild boar, domestic pigs and overlapping clusters [82]. Similar results were obtained for the time period 2017-2019 [87]. These studies indicate that the virus was able to persist in wild boar without constant reintroduction from domestic pigs in this region.…”
Section: Russian Federation (Rf)supporting
confidence: 75%
“…Spatial analysis of data from the RF obtained between 2007 and 2013 revealed clusters of ASF in wild boar, domestic pigs and overlapping clusters [82]. Similar results were obtained for the time period 2017-2019 [87]. These studies indicate that the virus was able to persist in wild boar without constant reintroduction from domestic pigs in this region.…”
Section: Russian Federation (Rf)supporting
confidence: 75%
“…Выявленные пространственно-временные закономерности распространения вспышек АЧС в субъектах РФ дают возможность предположить, что даже при наличии низкой плотности популяции кабана (менее 0,25 особи на 1000 га площади охотничьих угодий) сохраняется возможность передачи возбудителя от инфицированных объектов восприимчивым животным и распространения вируса в окружающей среде [41,42] Неоднократно в литературных источниках охота указывается как фактор риска распространения АЧС в связи с потенциальными миграциями кабанов в результате охотхозяйственной деятельности человека. Поэтому при обнаружении инфицированного вирусом АЧС кабана и установлении карантина на территории охотничьего угодья рекомендуют прекратить все возможные виды охоты в пределах зоны наблюдения, кроме мероприятий по регулированию численности кабана специально обученными людьми с соблюдением необходимых мер по недопущению передвижения животных за периметр данной зоны [43,44].…”
Section: выявление зависимости возникновения вспышек ачс среди кабано...unclassified
“…In some cases, the deaths of wild boar from ASF were registered near farms [4,16]. Spatiotemporal analysis in the Russian Federation showed that ASF outbreaks in both domestic pigs and wild boars correlated to each other [17,18]. The spread of ASF in European countries demonstrated the significance of the wild boar population density factor, although the wild boar was not the original cause of the infection.…”
Section: Introductionmentioning
confidence: 99%